An AI-Assisted Pragmatic Analysis of Speech Acts in Donald Trump's 2025 Speeches on the U.S.–Iran Conflict - Anhar; Hasbaini (Jurnal Inotera, 2025)
Political speeches play a significant role in shaping public opinion, legitimizing government policies, and influencing international perceptions, particularly during periods of military conflict. This study investigates the use of speech acts in Donald Trump's speech concerning the United States' military operation against Iran by applying Searle's Speech Act Theory. The objectives of the study are to identify the types of speech acts employed, determine their illocutionary functions, and examine how these speech acts contribute to the speaker's communicative intentions. This research adopts a qualitative descriptive approach using document analysis. The data consist of 62 utterances extracted from the official transcript of the speech, which were classified according to Searle's five categories of speech acts and analyzed based on their contextual illocutionary functions. The findings reveal that assertive speech acts are the most dominant, accounting for 67.7% of the total utterances, followed by directive (17.7%), commissive (9.7%), and expressive speech acts (4.8%), while declarative speech acts do not occur. The predominance of assertive speech acts indicates that the speech primarily functions to present military developments as factual information, justify government actions, and reinforce presidential authority. Meanwhile, directive and commissive speech acts encourage public support and communicate future commitments, whereas expressive speech acts mainly establish rapport with the audience. The absence of declarative speech acts suggests that the speech emphasizes persuasion and political legitimization rather than institutional action. These findings demonstrate that speech acts serve not only as linguistic expressions but also as strategic rhetorical devices for constructing political narratives and influencing public perception. This study contributes to the growing body of pragmatic research on political discourse by illustrating the applicability of Speech Act Theory in analyzing contemporary presidential communication during international conflict